A Pragmatic Analysis On Expressive Utterances Found In Rio De Janeiro Movie (2011) Manuscript - Susanti, Eni; , Drs. Sigit Haryanto, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research aims at describing the variation of the language forms of expressive utterances and describing the linguistic form of the speaker's intentions of expressive utterance in the Rio de Janeiro movie manuscript. The type of this research is descriptive qualitative research which the writer uses documentation and observation method as the method of collecting data. The data of this research are films which contain expressive utterances that are found in the data source that is Rio de Janeiro movie manuscripts. The result of the research show that firstly, the language forms of expressive utterances in movie manuscript is expressive sentences which are analysisinto declarative sentence 19,6%, interrogative sentences 16,3% and imperative sentences 18,5%. Secondly, the speaker's intentions of expressive utterances are Thanking 2,2%, Appologizing 2,2%, Blamming7,6%, Accusing utterance 9,8%.